(untitled) (Architecture Image Studies, 2025)
The construction industry plays a significant role in Malaysia’s economy; however, late payments remain a critical issue that disrupts projects and impacts financial stability. This study analyzes the primary causes of late payments in privately funded projects from the perspective of G7 contractors relying on the PAM Form of Contract and registered with the Construction Industry Development Board (CIDB). Questionnaires based on existing studies were distributed through random sampling using a quantitative methodology. The research focused on 15 key aspects categorized under three main headings: general characteristics, disputes, and human factors. Additionally, it considered post-pandemic impacts, which have often been overlooked in previous studies. Data analysis was conducted using SPSS and Smart PLS. The main variables identified include financial market volatility, inflation, employers withholding payments, ineffective financial management, lack of funds allocated for variation orders, banks refusing credit, conflicts over authorized payment amounts, certification delays, ambiguous contract terms, policy changes, and violations of prompt payment practices. After testing three hypotheses, recommendations were made for more equitable terms, such as implementing a Payment Security Bond and an associated contractual clause. By enhancing the financial sustainability and resilience of Malaysia’s construction industry, the report offers practical strategies to improve payment procedures, benefiting contractors, legislators, and industry stakeholders.